The Effect of Heat Treatment on Hardness and Microstructure of Al-Cu Squeeze Casting Product - Ali Saifullah; Ferdian Reynaldi; Iis Siti Aisyah; Achmad Fauzan Heri Soegiharto (University of Muhammadiyah Malang, 2019)
This research was conducted with the purpose of knowing the change mechanical properties of Al - Cu squeeze casting product which applied heat treatment and quenching. This study uses Al with the addition of 2% and 4% Cu,with the squeeze casting pressures applied are 100, 200, 300 and 400 bar. Heat treatment temperature constant at 520 ° C and 90 minute holding time. The heat treatment results were observed using Optical Microscopy with 800 times magnification and the hardness was measured using the Vickers hardness test method. . The highest result of hardness is on the pressure 400 bar with the addition of 4% Cu which is 120.53 VHN and the average percentage of the most Al2Cu compounds is 23.125%. Heat treatment followed by quenching process significantly increase the hardness, it is because of the more solid and smaller granular shape due to quenching